Healthy eating and physical activity environments in out-of-school hours care: an observational study protocol. Issue 9 (28th September 2020) - Crowe, Ruth; Probst, Yasmine; Norman, Jennifer; Furber, Susan; Franco, Lisa; Stanley, Rebecca M.; Vuong, Cecilia; Wardle, Karen; Davies, Marc; Ryan, Sarah; Okely, Anthony D.
Abstract : Introduction: Childcare settings have been widely identified as important venues for promoting healthy lifestyles to children. Out-of-school hours care (OSHC) is a rapidly growing childcare service, yet there has been limited research reported on healthy eating and physical activity (HEPA) environments within the Australian OSHC setting. This research aims to describe the HEPA environments related to foods and beverages served, staff behaviours and child physical activity levels across two local health districts within New South Wales, Australia. This study will provide evidence to support future interventions and policies in Australian OSHC settings. Methods and analysis: A cross-sectional study design will be used to describe the food and beverages provided and child activity levels, and report on environmental correlates. OSHC programmes will be visited on non-consecutive weekdays between 2018 and 2020. The frequency of foods and beverages offered will be observed and categorised into food groups aligned to the Australian Dietary Guidelines. Children's physical activity will be measured using ActiGraph wGT3X-BT accelerometers. Staff behaviour will be captured via direct observation and the System for Observing Staff Promotion of Activity and Nutrition. Short interviews with programme directors will gather contextual information about OSHC practices and policies. Ethics and dissemination: Findings will be disseminated through peer-reviewed scientific journals, conference presentations and individualised feedback to each participating service. Ethical approval was granted by the University of Wollongong Human Research Ethics Committee (HE17/490).